Hawke's fury - Wortham, Reavis Z (Wortham, Reavis Z. Sonny Hawke thriller., 2020)
Border patrol agents are being ambushed along the Big Bend region of West Texas, a notorious drug corridor running east and west across the Lone Star State. They're not the only targets. A film production depicting human trafficking in the area has been attacked by a brutal drug cartel. Into this lawless frontier steps Texas Ranger Sonny Hawke, ready and willing to dispense his own brand of justice. It's an all-out war with the thinnest line separating the good from the bad. Sonny knows the only way out is to aim straight and stand your ground . . .